2019
DOI: 10.1186/s12886-019-1257-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anterior segment changes after femtosecond laser LASIK and SMILE using a dual rotating Scheimpflug analyzer

Abstract: BackgroundTo compare the changes in the anterior segment after femtosecond laser in situ keratomileusis (FS-LASIK) and small incision lenticule extraction (SMILE) using a dual rotating Scheimpflug (DRS) analyzer (Galilei®; Ziemer Ophthalmology, Port, Switzerland).MethodsA total of 218 eyes of 109 patients who underwent FS-LASIK or SMILE for myopic correction were retrospectively studied. Ninety-eight eyes of 49 patients who underwent FS-LASIK were compared to 120 eyes of 60 patients treated with SMILE. A DRS a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…We found that there were significant decreases in ACD, ACA, and ACV after FS-LASIK in both the low age group and high age group of patients with myopia, consistent with the results of previous studies [ 21 24 ], and the ACD became shallower in both two groups approximately to the same degree. Mean preoperative ACD in the high age group of myopia (2.85 ± 0.24 mm) was significantly lower than that of the low age group (3.19 ± 0.23 mm), the reason for which was the decrease in ACD with age [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that there were significant decreases in ACD, ACA, and ACV after FS-LASIK in both the low age group and high age group of patients with myopia, consistent with the results of previous studies [ 21 24 ], and the ACD became shallower in both two groups approximately to the same degree. Mean preoperative ACD in the high age group of myopia (2.85 ± 0.24 mm) was significantly lower than that of the low age group (3.19 ± 0.23 mm), the reason for which was the decrease in ACD with age [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…The limitations of this study are as follows: First, we only measured the anterior chamber index values of patients 3 months postoperatively, but the literature has followed up the anterior chamber values from 1 week to 6 months after surgery, although they still come to a conclusion that is consistent with ours [ 18 , 21 ]. Second, because this is a retrospective study and did not verify the effect of accommodation on the anterior chamber, relevant prospective studies need to be further improved to explore the effect of accommodation on the anterior segment before and after surgery.…”
Section: Discussionmentioning
confidence: 63%
“…20 This finding was consistent with the previous studies using MMC in different refractive correction surgeries. 32 …”
Section: Discussionmentioning
confidence: 99%
“…20 This finding was consistent with the previous studies using MMC in different refractive correction surgeries. 32 Although contradictory findings were observed with respect to significant changes in the different corneal endothelial indices and MMC exposure and application in the literature, 20,33 similar prospective studies investigating the effect of MMC on corneal endothelium post-refractive correction reveal no differences in the endothelial indices after 6-12 months postoperatively. 20,25 This suggests that we may need longer follow-ups to investigate the long-term safety and efficacy of MMC on corneal endothelium after T-PRK.…”
mentioning
confidence: 99%
“…This seems to go hand in hand with trials on ablation depth, overall CT reduction, or LT, which show a higher ablation than expected. 28 30 A recently published trial by Luo et al 31 showed significant deviation from targeted stromal reduction in SMILE eyes but fs-LASIK as well. In the SMILE group, the stromal reduction was overestimated by 20.05 ± 5.92 µm and overestimated by 8.21 ± 8.14 µm in fs-LASIK eyes.…”
Section: Discussionmentioning
confidence: 99%